background image

Proof.

A

and

B

are separable accordingly obvious 20 in [3].

Then apply [1] taking in account the theorem 12.

Theorem 32.

Let

A

and

B

are starrish join-semilattices. Then:

1.

f

FCD

(

A

;

B

)

g

x

=

h

f

i

x

B

h

g

i

x

for every

x

A

;

2.

f

FCD

(

A

;

B

)

g

=[

f

]

[

g

]

.

Proof.

1. Let

α

X

=

def

h

f

i

x

B

h

g

i

x

;

β

Y

=

def

h

f

1

i

y

A

h

g

1

i

y

for every

x

A

,

y

B

. Then

y

B

α x

y

B

h

f

i

x

y

B

h

g

i

x

x

A

h

f

1

i

y

x

A

h

g

1

i

y

x

A

h

f

1

i

y

A

h

g

1

i

y

x

A

βy.

So

h

= (

A

;

B

;

α

;

β

)

is a pointfree funcoid. Obviously

h

f

and

h

g

. If

p

f

and

p

g

for some

p

FCD

(

A

;

B

)

then

h

p

i

x

⊇ h

f

i

x

B

h

g

i

x

=

h

h

i

x

that is

p

h

. So

f

FCD

(

A

;

B

)

g

=

h

.

2.

x

f

FCD

(

A

;

B

)

g

y

y

B

f

FCD

(

A

;

B

)

g

x

y

B

h

f

i

x

B

h

g

i

x

y

B

h

f

i

x

y

B

h

g

i

x

x

[

f

]

y

x

[

g

]

y

for every

x

A

,

y

B

.

Theorem 33.

Let

f

is a pointfree funcoid from a separable poset

A

to a separable poset

B

. If

h

f

i

is an injection, then

h

f

i

is an order embedding

A

B

.

Proof.

Suppose

x

y

but

h

f

i

x

+

h

f

i

y

.

Then by separability of

B

there exist

z

h

f

i

y

such that

z

≍ h

f

i

x

.

Thus

h

f

1

i

z

x

and

h

f

1

i

z

y

what is impossible for

x

y

.

Corollary 34.

Let

f

is a pointfree funcoid from a separable poset

A

to a separable poset

B

. If

h

f

i

is a bijection

A

B

, then

h

f

i

is an order isomorphism

A

B

.

3.5 More on composition of pointfree funcoids

Proposition 35.

[

g

f

]=[

g

]

◦h

f

i

=

h

g

1

i

1

[

f

]

for every composable pointfree funcoids

f

and

g

.

Proof.

x

[

g

f

]

y

y

Dst

g

h

g

f

i

x

y

Dst

g

h

g

ih

f

i

x

⇔ h

f

i

x

[

g

]

y

x

([

g

]

◦h

f

i

)

y

for every

x

A

,

y

B

. Thus

[

g

f

]=[

g

]

◦h

f

i

.

[

g

f

]=[(

f

1

g

1

)

1

]=[

f

1

g

1

]

1

=([

f

1

]

◦h

g

1

i

)

1

=

h

g

1

i

1

[

f

]

.

Theorem 36.

Let

f

and

g

are pointfree funcoids and

A

=

Dst

f

=

Src

g

is an atomic poset. Then

for every

X ∈

Src

f

and

Z ∈

Dst

g

X

[

g

f

]

Z ⇔ ∃

y

atoms

A

: (

X

[

f

]

y

y

[

g

]

Z

)

.

Proof.

y

atoms

A

: (

X

[

f

]

y

y

[

g

]

Z

)

⇔ ∃

y

atoms

A

: (

Z

Dst

g

h

g

i

y

y

A

h

f

iX

)

⇔ ∃

y

atoms

A

: (

Z

Dst

g

h

g

i

y

y

⊆ h

f

iX

)

⇒ Z

Dst

g

h

g

ih

f

iX

⇔ X

[

g

f

]

Z

.

Reversely, if

X

[

g

f

]

Z

then

h

f

iX

[

g

]

Z

, consequently exists

y

atoms

A

h

f

iX

such that

y

[

g

]

Z

;

we have

X

[

f

]

y

.

Theorem 37.

Let

A

,

B

,

C

are posets and

B

is atomic. Then:

1.

f

(

g

FCD

(

A

;

B

)

h

) =

f

g

FCD

(

A

;

C

)

f

h

for

g, h

FCD

(

A

;

B

)

and

f

FCD

(

B

;

C

)

.

Pointfree funcoids

7